Maternal Infection Is a Risk Factor for Early Childhood Infection in Filariasis. - Madhusmita Bal; Prakash K Sahu; Nityananda Mandal; Ashok K Satapathy; Manoranjan Ranjit; Shatanu K Kar (Public Library of Science (PLoS), 2015)
BACKGROUND:Global Program to Eliminate Lymphatic Filariasis (GPELF) launched by WHO aims to eliminate the disease by 2020. To achieve the goal annual mass drug administration (MDA) with diethylcarbamazine (DEC) plus albendazole (ABZ) has been introduced in all endemic countries. The current policy however excludes pregnant mothers and children below two years of age from MDA. Since pregnancy and early childhood are critical periods in determining the disease outcome in older age, the present study was undertaken to find out the influence of maternal filarial infection at the time of pregnancy on the susceptibility outcome of children born in a community after implementation of MDA for the first time. METHODOLOGY AND PRINCIPAL FINDINGS:The participants in this cohort consists of pregnant mothers and their subsequently born children living in eight adjacent villages endemic for filarial infections, in Khurda District, Odisha, India, where MDA has reduced microfilariae (Mf) rate from 12% to 0.34%. Infection status of mother and their children were assessed by detection of Mf as well as circulating filarial antigen (CFA) assay. The present study reveals a high rate of acquiring filarial infection by the children born to infected mother than uninfected mothers even though Mf rate has come down to < 1% after implementation of ten rounds of MDA. SIGNIFICANCE:To attain the target of eliminating lymphatic filariasis the current MDA programme should give emphasis on covering the women of child bearing age. Our study recommends incorporating supervised MDA to Adolescent Reproductive and Sexual Health Programme (ARSH) to make the adolescent girls free from infection by the time of pregnancy so as to achieve the goal.